Wednesday

April 16, 2014

April 16, 2014

Posted by **Anne** on Monday, August 13, 2012 at 11:02am.

- Algebra -
**Steve**, Monday, August 13, 2012 at 11:15amcombine terms to get

(a^2 - 4a - a + 6)/(a^2-a-6)

= (a^2-5a+6)/(a^2-a-6)

= (a-3)(a-2)/((a-3)(a+2))

= (a-2)/(a+2)

if a≠3

**Related Questions**

algebra - 3(a+2)=4a I multiply 3*a+3*2=4a so 3a+6=4a I added 3a to 4a/ =7a and ...

College Algebra - Solve each equation. If an equation has no solution, so ...

Algebra - Square root of (q^2+7q+6) minus q minus 3=0. Minus 3 and minus q are ...

?? - 2a-3 x a+2 --------------- 4a-6 <-ok why does 4a plus 2a^2-3a <3b = ...

algebra - Subtract (4a^3+3b^3)-(2a^3+4a^2b-_5ab^2+3b^3) is the answer 2a^3+4a^2b...

algebra - What is the equation in standard form of a parabola that models the ...

Algebra help - Solve by completing the square x2 - 2x - 5 = 0. Help please a)1 ...

algebra - Factor 2x squared minus 5x minus 3.

algebra,math - Solve the equation. 4 times the square root of x minus 5 minus 8...

Algebra - Factor 2xsquared minus 5x minus 3.